PELATIHAN DIGITAL MARKETING BAGI UMKM UNTUK MENINGKATKAN DAYA SAING DI ERA DIGITAL - Ilham, Ratih Milati; Utami Puspitasari, Ratih Hesty; Amin, Fatkhul (LPPM Universitas Bina Bangsa, 2025)
Digital marketing has become one of the main strategies in increasing the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the digital era. This article aims to describe community service activities in the form of digital marketing training for MSMEs. This activity aims to increase the digital literacy of MSME players, expand market reach, and increase income through digital platforms. The methods used in this activity include socialization, interactive training, and mentoring. The results of the activity show that MSME players are able to understand the basic concepts of digital marketing, operate digital platforms, and utilize social media and marketplaces to increase sales.